2019
DOI: 10.1097/md.0000000000016186
|View full text |Cite
|
Sign up to set email alerts
|

A predictive model for progression of CKD

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
1
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 18 publications
3
38
1
2
Order By: Relevance
“…Chang et al retrospectively reviewed and analyzed 1549 CKD patients who participated in the “Public health insurance Pre-ESRD preventive program and patient health education program” to establish an optimal prediction model for CKD progression. They found that the influencing factors with the best explanatory power included age, serum creatinine (Cr), urea nitrogen, and comorbidity with diabetes [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chang et al retrospectively reviewed and analyzed 1549 CKD patients who participated in the “Public health insurance Pre-ESRD preventive program and patient health education program” to establish an optimal prediction model for CKD progression. They found that the influencing factors with the best explanatory power included age, serum creatinine (Cr), urea nitrogen, and comorbidity with diabetes [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the course of renal disease progression is heterogeneous and complex in T2DM, due to individual patient characteristics and disease‐specific conditions 12,13 . Although these studies had identified risk factors for the development of advanced kidney disease or a rapid decline in renal function in T2DM with CKD, the findings of these studies were limited due to small population sizes and short‐term follow‐up 9–13 . In addition, reported risk and protective factors for CKD progression among T2DM patients were conflicting 14–16 …”
Section: Introductionmentioning
confidence: 99%
“…Cr in the blood is mainly produced as a metabolite of muscle activity and is excreted daily by the kidney with urine. When renal function is impaired, Cr products cannot be completely excreted, resulting in elevated serum Cr concentration [23]. Bertille et al reported increased levels of Cr and CysC in males when compared with those in females, and they were higher in subjects over 55 years old [24].…”
Section: Discussionmentioning
confidence: 99%